Penyelesaian Perkara Tindak Pidana Kekerasan dalam Rumah Tangga berdasarkan Konsep Restorative Justice (Studi Putusan Pengadilan) - Mo’amer Kohsad; Ayu Izza Elvany (Fakultas Hukum Universitas Islam Indonesia, 2024)
Restorative Justice is an approach that focuses on the need to improve the relation between the perpetrator, the community and the victims affected by the conflict, as well as the position of the parties who seem to be marginalized by the current criminal justice system mechanism. In Indonesia, Restorative Justice has been implemented, yet in several court decisions, the defendant still received a prison sentence from the judge. This research aims to analyse the efforts of Restorative Justice in cases of domestic violence did not succeed in the decision and whether the efforts of Restorative Justice were considered by the judge in imposing a sentence on the defendant in a case of domestic violence. This research uses normative legal research, with a statutory approach and a case approach. The results of this study are first, the failure of Restorative Justice efforts in several court decisions is caused by several factors. Second, Restorative Justice efforts between victim witnesses and defendants are included in mitigating circumstances and have a positive impact on the judge's consideration.